Genome-Wide Identification and Stage-Specific Expression Profile Analysis Reveal the Function of Ribosomal Proteins for Oogenesis of Spodoptera litura - Sun, Ranran; Liu, Jin; Xu, Yuanhao; Jiang, Liwei; Li, Yun; Zhong, Guohua; Yi, Xin (Frontiers in Physiology, 2022)
Ribosomal proteins (Rps) are indispensable in ribosome biogenesis and protein synthesis, which tightly correlate with cell growth and proliferation in different physiological processes across species. Up to now, genes coding for Rps have been identified and studied in many species, however, their information still remains elusive in many insect species, especially in Spodoptera litura. In this study, 81 Rp genes were identified from S. litura genome and were mapped to their positions on the chromosomes. In addition, their physical and chemical properties, gene structure, phylogenetic relationships, targeted microRNAs were also analyzed. Gene ontology analysis disclosed that Rp genes were closely associated with processes related to ribosome biosynthesis, proteins translation processing, molecular binding activities. The quantitative real-time PCR (qRT-PCR) revealed expression profiles of Rp genes varied in different stages of oogenesis, and found that most Rp genes accumulated in previtellogenesis stage. This study described the comprehensive genome-wide analysis of Rp gene family in agricultural pests, which provided foundation for further characterizing the roles of Rps in oogenesis of insects, and some Rp genes may further serve as targets for innovative pest control.